Ancient History of Arabian Peninsula and Semitic Arab Tribes - Mohd. Shamsuddin, Salahuddin; Hj. Ahmad , Siti Sara Binti (Advances in Social Sciences Research Journal, 2020)
In this article we introduced first the ancient history of Arabian Peninsula, and pre-Islamic era and then we focused a spot light on the people of Arabian Peninsula, highlighting the four waves of migration of Semitic Arabs from the southern to northern Arabian Peninsula, then we mentioned the situation of Northern Arabs and their tribal fanaticism, then we differentiated between Qahtaniyya and Adnaniyya Arab tribes including their three Classes: Destroyed Arab, Original Arab and Arabized Arab. We also explained the tribal system in the pre-Islamic era, indicating the status of four pillars of the tribal system: Integration and alliance among the tribes Tribal Senate or Parliament Tribes and sovereignty over the tribes Members of the tribes and their duties towards their tribal society In the end we described the master of Arab tribe who was the brightest person had a long experience and often had inherited his sovereignty from his fathers to achieve a high status, but it does not mean that he had a broad sovereignty, as his sovereignty was symbolic. He had no rights except that he was obeyed and respected by everyone. We tried to mention all these points with some further details.